Implementasi Moderasi Beragama Sebagai Upaya Pembentukan Karakter Moderat MTsS Nur Bahri Desa Bubun - Nugraha, Babang Prima; Shaliha, Faradiba; Fitriani, Fitriani; Siagian, Nurul Hikmah; Nasution, Nur Khadijah; Ramadhan, Muhammad Abrar (LPPPI Publishing, 2024)
Religious moderation plays an important role in everyday life, helping individuals to avoid radical and extreme attitudes in the face of diversity and difference. The lack of understanding about religious moderation, especially in MTsS Nur Bahri, Bubun Village, Tanjung Pura District, Langkat Regency, is the reason the author raises this issue. This article aims to provide an overview of the implementation of religious moderation and how it can shape tolerant, patriot, socially concerned, and just characters. The author uses a qualitative research approach with a case study method, involving observation and discussion. Data were collected through seminars that were part of the real work lecture (KKN) activities. The findings showed that religious moderation at MTsS Nur Bahri in Bubun Village received a positive response and supported its implementation. One of the pillars of religious moderation that has been implemented is the attitude of tolerance towards differences, both in terms of religion, ethnicity, and opinion. This shows that the implementation of religious moderation in the school has succeeded in forming a tolerant attitude among teachers and students.